CURRENT PROBLEMS AND DEVELOPMENT PRINCIPLES OF CONTINUING PROFESSIONAL EDUCATION - Shaxnoza Mirzaaxmadovna Mirzaraxmonova (Web of Journals Publishing, 2024)
The article deals with dual professional competence as dual content of the theoretical basis of professional education and development of the system.
Keywords: Vocational-pedagogical education, Second World War, innovation cycles, technical direction, pedagogical activity, professional training, professional education teacher.